The Potential of Korean Drama as Edutainment Media to Improve Mental Health Literacy: Content Analysis of “Daily Dose of Sunshine” - Linadi, Kinanthi; Haryati, Tuningsih (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2025)
Background: Mental health literacy is currently very much needed considering the high rates of psychological issues in Indonesia and the stigma that still exists towards individuals with psychological issues. The emergence of the Korean Wave in Indonesia has made Korean dramas one of the potential media for enhancing mental health literacy. Objective: This research aims to analyze the content (characters, setting, visual codes, and key messages) related to mental health that conveyed through the drama “Daily Dose of Sunshine”. Methods: This study uses a qualitative method with John Fiske's semiotic analysis, including analysis at the levels of reality, representation, and ideology. Results: The reality analysis focuses on visual elements, display code, dress code, makeup code, how-to-speak code, gesture code, expression code, and environment code that depict the interaction between health workers, mental health clinic patients, and their families. The representation analysis focuses on the dialogue analysis, which contains key messages about mental health. The representation analysis results indicate six key messages conveyed through the dialogue between health workers and individuals with psychological disorders. In the ideology analysis, key mental health messages were found, including the importance of managing stress for mental health; the importance of seeking professional mental health help; the issue of stigma towards people with psychological disorders; the dangers of self-diagnosis; the role of family in supporting the recovery of individuals with psychological disorders; and the notion that anyone can experience psychological disorders. Conclusion: From this study, it can be seen that Korean dramas are a form of edutainment media that can disseminate key mental health messages to a broad audience. Therefore, it is hoped that there will be further development of health promotion media in the form of series to promote health issues in Indonesia, particularly regarding mental health and well-being.